General switch‐and‐examine relaying for demodulate‐and‐forward cooperative diversity. (18th October 2014) - Chau, Yawgeng A.; Al‐Harbawi, Mostafa
Summary: Two new demodulate‐and‐forward schemes of multi‐relay cooperative diversity with switch‐and‐examine relaying (SER) are analyzed. To reduce relay usage and enhance bandwidth efficiency, the two new cooperative diversity schemes employ a switch‐based relay selection. The proposed schemes consume less communication resource than regular relaying schemes, such as the selection combining (SC) or maximal ratio combining (MRC) schemes that always use all relays, and also achieve better performance than distributed switch‐and‐stay schemes. In the first scheme, the decision statistic for relay usage and selection is based on the signal‐to‐noise ratio (SNR). In the second scheme, the log‐likelihood ratio (LLR) of received signals is used for the decision of relay usage and selection. With the two SER schemes, the bit error probability (BEP) of binary phase shift keying (BPSK) and the average number of used paths are derived and expressed in closed‐form for the independent and identically distributed (i.i.d.) Rayleigh fading channels. Numerical and simulation results are presented for performance illustrations. According to the numerical results, the LLR‐based SER not only achieves a lower BEP but also consumes less relay resource than the SNR‐based SER. Furthermore, the LLR‐based SER scheme even outperforms the corresponding SNR‐based SC scheme for a range of average SNR. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : To reduce relay usage and enhance bandwidth efficiency, two new demodulate‐and‐forward schemes of multi‐relay cooperative diversity with switch‐and‐examine relaying (SER) are analyzed. The signal‐to‐noise ratio (SNR) and the log‐likelihood ratio (LLR) are used as the decision statistic for relay usage and selection in the two schemes, respectively. For cooperative diversity, the LLR‐based SER not only achieves a lower bit error probability but also consumes less relay resource than the SNR‐based one and even outperforms the SNR‐based SC scheme for a range of average SNR.